Porokeratosis Concurrent and Coexistent with Psoriasis Vulgaris - Helm, Melissa M; Kalb, MD, Robert E; Dhafir, MD, Mazin (North American Journal of Medicine and Science, 2017)
Disseminated superficial actinic porokeratosis is a rare photodistributed disorder that has occasionally been reported in association with psoriasis. Treatment of psoriasis with phototherapy may trigger the onset of porokeratosis in some cases. In other cases, the coexistence of these disorders may be coincidental. Clinical inspection of lesions of coexisting porokeratosis and psoriasis reveals increased erythema, diffuse and thickening of cornoid lamellae, as well as increased scale. These subtle yet characteristic features allow for correct clinical diagnosis and are associated with corollary histologic findings. Psoriatic changes occurring in lesions of porokeratosis are likely explained by the isomorphic (Koebner) response. Physicians should be aware that these two disorders can co-exist in order to ensure correct diagnosis and proper treatment. [N A J Med Sci. 2017;10(2):70-72. DOI: 10.7156/najms.2017.1002070]